Association of C‐reactive protein (CRP) rs1205 and rs2808630 variants and risk of cancer. Issue 11 (24th April 2020) - Pan, Hai‐Yan; Mi, Yuan‐Yuan; Xu, Kai; Zhang, Ze; Wu, Hao; Zhang, Wei; Yuan, Wei; Shi, Li; Zhang, Li‐Feng; Zhu, Li‐Jie; Zuo, Li
Abstract: The correlation between rs1205, rs2808630 variants of C‐reactive protein (CRP) gene and susceptibility of cancer has been assessed previously, but with conflicting results. We adopted odds ratios (ORs) with 95% confidence intervals (CIs), in silico tools and enzyme‐linked immunosorbent assay (ELISA) analysis to evaluate this association. Totally, 10, 614 cancer subjects and 33, 294 controls were involved in the pooled analysis. When all the studies were pooled, no significant correlation was indicated between the two variants and cancer risk. However, in stratification analysis by ethnicity, we found that CRP rs1205 C>T polymorphism was associated with an elevated risk of cancer in Asians (T‐allele vs. C‐allele, OR = 1.20, 95% CI = 1.06–1.36, p heterogeneity  = .226; TT vs. CC, OR = 1.48, 95% CI = 1.14–1.93, p heterogeneity  = .089). Similar findings were observed for rs2808630 variant. In silico tools showed that lung adenocarcinoma participants with high CRP expression may have shorter overall survival time than low expression group. ELISA analysis indicated that CRP expression in prostate adenocarcinoma subjects with TT + TC genotypes was statistically higher than in those with CC genotypes. CRP rs1205 C>T and rs2808630 T>C polymorphism may be associated with cancer risk, especially for Asians. Abstract : We adopted odds ratios (ORs) with 95% confidence intervals (CIs), in silico tools and enzyme‐linked immunosorbent assay (ELISA) analysis to evaluate the correlation between CRP rs1205, rs2808630 variants and susceptibility of cancer. We found that CRP rs1205 C>T and rs2808630 T>C polymorphism may be associated with cancer risk, especially for Asians.